Short Communication: Stimulatory effect of Curcuma mangga on immune response against Staphylococcus aureus - Yuandani YUANDANI; SONY EKA NUGRAHA; LIA LAILA; SETIA DAME SILABAN; FADHILAH RAMADHANI (Smujo International, 2020)
Abstract. Yuandani, Nugraha SE, Laila L, Silaban SD, Ramadhani F. 2020. Short Communication: Stimulatory effect of Curcuma mangga on immune response against Staphylococcus aureus. Nusantara Bioscience 12: 109-113. Recently, the ethanol extract of Curcuma mangga Val. rhizomes were found to have immunomodulatory activity by enhancing phagocytic ability. This study was carried out to evaluate the effect of C. mangga rhizomes on antibody titer and delayed-type hypersensitivity response in normal and doxorubicin-induced rats against Staphylococcus aureus. The extract was administered orally at doses of 100, 200, and 400 mg/kg body weight (bw) to rats for 72 hours prior to sensitization of Staphylococcus aureus, then continued for 14 days. Doxorubicin (4.67 mg/kg bw) was administered on days 8 and 11 to suppress the immune system. The antibody titer of normal and immune-suppressed rats after the treatment with C. mangga ethanolic extract was significantly higher than the rats with negative control (P<0.05). Ethanol extract of C. mangga also demonstrated stimulation on delayed-type hypersensitivity response which was indicated by the increase of paw volume. The extract at dose of 400 mg/kg bw showed higher immunostimulatory activity than Levamisole as a positive control. The results indicated that the ethanol extract of C. mangga shows immunostimulatory activity, confirming its potential to be developed as a therapeutic agent.